Transfer of tRNAs to somatic cells mediated by Sendai-virus-induced fusion. - Kaltoft, K (1976)
tRNAs from yeast (tRNAPhe and 4S RNA) and Escherichia coli (suIII+ tRNAITyr) have been transferred to mouse cells by means of a two-step transfer procedure [Loyter, Zakai, and Kulka (1975) J. Cell Biol. 66, 292-304; Schlegel and Rechsteiner (1975) Cell 5, 371-379]. In the first stage of the transfer tRNAs were incorporated into rabbit red blood cells (RBCs). Thereafter, the loaded erythrocytes were fused with recipient mouse cells by means of Sendai virus. At least 0.3-0.4% of the total input of tRNA used to load the RBCs could be transferred to mouse cells. Of the tRNA incorporated in the mouse cells, at least 50% could be recovered in the form of intact tRNA molecules when yeast 4S RNA was used. With E. coli suIII+ tRNAITyr a rather smaller proportion of the tRNA remained intact (33%). Although the loading of tRNA into RBCs is not essential for its uptake, we find that the transfer is four times more efficient with RBCs as a vehicle for the injection. Significantly, a fraction (2%) of the recipient cells possessed much more incorporated tRNA than the average cell when Sendai virus and loaded RBCs were used. Such cells were not found in control experiments in which tRNA uptake was induced by Sendai virus alone.